2018
DOI: 10.21307/sjcapp-2018-009
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Brief Child and Family Phone Interview by comparison with Longitudinal Expert All Data diagnoses in outpatients

Abstract: Background: The Brief Child and Family Phone Interview (BCFPI) is a standardized intake and follow-up interview used in child and adolescent mental health services (CAMHS). Although it has shown good validity compared with other measures using parent reports, it has not yet been compared with diagnoses derived from a Longitudinal Expert All Data (LEAD) procedure, which includes information from separate diagnostic interviews with parent(s) and child. The aim was to compare the BCFPI evaluation in an outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…There were more boys (n = 102, 54.8%) than girls. The sample studied was compared to a concurrent and consecutive sample (n = 5641) of help-seeking CAP outpatients [22]. The sample was no different in proportions of children versus adolescents or boys versus girls but slightly more symptomatic in internalizing (d � 0.3, p< 0.001) and in externalizing symptoms (d � 0.5, p< 0.001).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were more boys (n = 102, 54.8%) than girls. The sample studied was compared to a concurrent and consecutive sample (n = 5641) of help-seeking CAP outpatients [22]. The sample was no different in proportions of children versus adolescents or boys versus girls but slightly more symptomatic in internalizing (d � 0.3, p< 0.001) and in externalizing symptoms (d � 0.5, p< 0.001).…”
Section: Participantsmentioning
confidence: 99%
“…Further, a lower AUC to discriminate mood disorder was noted in MFQ-parent from clinical as opposed to non-clinical studies [11]. Earlier studies have suggested cut-offs based on maximum separation of 27-29 (MFQ-child) and [21][22][23][24][25][26][27] (MFQ-parent) [11][12][13]16]. Suggested cut-offs favouring sensitivity were 26-28 (MFQ-child) and 22 (MFQ-parent) [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…The results are presented as a T-score for each subscale with standardized norms for age and gender. BCFPI also examines the child's overall functioning, family functioning, family distress, parental depression, neglect and abuse [26]. The parameter family situation consists of two subdomains, family comfort and family activity.…”
Section: Brief Child and Family Phone Interview (Bcfpi)mentioning
confidence: 99%
“…response given from the staff), methods for parenting, influence on decision, and benefit of the assessment. The BCFPI has shown overall good validity in different settings [26][27][28] and its broad approach has proven useful in evaluating mental health services [29][30][31][32].…”
Section: Brief Child and Family Phone Interview (Bcfpi)mentioning
confidence: 99%
See 1 more Smart Citation